A Heuristic Local Search Algorithm for Improving Cluster and Routing Stability in Sensor Networks - Manoharan, L.; Ezil Sam Leni, A. (International Journal of Engineering and Technology, 2018)
Route selection using optimal nodes in Wireless Sensor Network (WSN) is a prominent task to improve network performance without deterioration. Intrinsic characteristics of the node, network traffic are some of the reason where routing algorithms fail to prove their consistency. In such cases, the conventional routing schemes must be equipped with additional network management features to retain network performance. This manuscript proposes a Heuristic Local Search (HLS) algorithm for improving routing efficiency of WSN. This search algorithm is backboned by clustering process; the cluster head is elected by satisfying balanced network metrics: energy and distance. Congestion preventive routing considers the same objective function in selecting an outside intermediate node that mitigates packet loss due to congestion. Implication of similar objective function under different constraints streamlines routing and prolongs the operation period of the cluster head. The process of the proposed HLS is evaluated using extensive simulation for the metrics: throughput, network lifetime, cluster head changes, energy utilization and packet loss ratio.